WORKOVER OPERATION IMPROVEMENT FOR WELLS WITH HIGH WELLHEAD ELEVATION AT âHUMAIRAâ AREA - Budi Rudiantoro, Agung
PT. Diamond Energy Indonesia (PT. DEI), located in Riau Province, is one of the largest oil producers in Indonesia. In responding to the dynamic fluctuations of oil and gas commodity prices in recent years, PT. DEI puts serious efforts to maintain oil production and reduce operational costs to assure their competitiveness in the oil and gas industry in the country. One of PT.DEI focus area is cost efficiency in the field of drilling and workover.